Saúde Sexual e Reprodutiva das Adolescentes - a Nossa Realidade - Oliveira Marques, C (2014)
Overview and Aims: Several behavioral and biological factors can make adolescents particularly vulnerable to unwanted pregnancies and sexually transmitted diseases. The aim of this study was to evaluate sexual behavior and contraceptive use patterns of a population of adolescents. Study Design: Retrospective study. Population: 163 female adolescents attending an Adolescence Unit for the first time, during 2010. Methods: Analysis of clinical charts and assessment of demographic data, smoking and drinking habits, drug use, gynecologic and obstetric history, sexual behavior and contraceptive use. Results: The mean age was 16.04 years (±1.32). 71.7% were students (of these, 70% had failed one or more years and were behind in their studies), 2.5% were working and 23.9% were neither studying or working. 95.1% had already had sexual intercourse and the mean age of first coitus was 14.53 years (±1.24). There was a history of at least one previous pregnancy in 77.3% of the cases. Before the first appointment at the AU, the contraceptive methods used were: the pill (33.2%, but 41.3% of these reported inconsistent use), and the condom (23.9%, with inconsistent use in 28.3% of these cases). 19.6% did not use any contraceptive method.. After counseling at the AU, 54% of the teenagers chose the contraceptive implant and 35% preferred the pill. Adolescents who had already been pregnant preferred a long acting method (namely, the contraceptive implant)in 61.9% of cases; those who had never been pregnant decided to use an oral contraceptive in 67.6% of cases (p<0.001). Conclusions: After counseling the number of teenagers using contraception increased. In this population there were a high number of adolescents with a previous pregnancy. This factor seems to have influenced the choice of the contraceptive method, with most of these adolescents choosing a long-acting method.